Peran Kepemimpinan Kepala Sekolah dan Kinerja Guru dalam Meningkatkan Kualitas Mutu Pendidikan pada SDI Cokroaminoto Surabaya - Lailatul Rohma Hadi; Iswati Iswati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The principal has an important role which is very helpful to the Cokroaminoto Islamic elementary school. in improving the quality of education, even though his role is only as PLT Principal, he carries out his duties well. Efforts to improve the quality of education are one of the factors in creating ideal education. This research wants to find out more about